Angiogenic Gene Signature Derived from Subtype Specific Cell Models Segregate Proneural and Mesenchymal Glioblastoma - Sharma, Aman; Bendre, Ajinkya; Mondal, Abir; Muzumdar, Dattatraya; Goel, Naina; Shiras, Anjali (Frontiers in Oncology, 2017)
Inter-tumoral molecular heterogeneity in glioblastoma identifies four major subtypes based on expression of molecular markers. Amongst them, the 2 clinically-interrelated subtypes, proneural and mesenchymal, are the most aggressive with proneural liable for conversion to mesenchymal upon therapy. Using 2 patient-derived novel primary cell culture models (MTA10 and KW10), we developed a minimal but unique 4 gene signature comprising of genes VEGF-A, VEGF-B and ANG1, ANG2 that effectively segregated the proneural (MTA10) and mesenchymal (KW10) glioblastoma subtypes. The cell culture preclassified as mesenchymal showed elevated expression of genes VEGF-A, VEGF-B and ANG1, ANG2 as compared to the other cell culture model that mimicked the proneural subtype. The differentially-expressed genes in these 2 cell culture models were confirmed by us using TCGA and Verhaak databases and we refer to it as a minimal multi-gene signature (MMS). We validated this MMS signature on human glioblastoma tissue sections with the use of immunohistochemistry on pre-classified (YKL-40 high or mesenchymal glioblastoma and OLIG2 high or proneural glioblastoma) tumor samples (n=30). MMS segregated mesenchymal and proneural subtypes with 83% efficiency using a simple histopathology scoring approach (P= 0.008 for ANG2 and P=0.01 for Ang1). Furthermore, MMS expression negatively correlated with patient survival. Importantly, MMS staining demonstrated spatiotemporal heterogeneity within each subclass, adding further complexity to subtype identification in glioblastoma. In conclusion, we report a novel and simple sequencing-independent histopathology-based biomarker signature comprising of genes VEGF-A, VEGF-B and ANG1, ANG2 for subtyping of proneural and mesenchymal glioblastoma.